The effect of neighboring images in generating meaning A reading of examples from the Maqamat of Jalal al-Din al-Suyuti - خضر, يعرب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research is an attempt to determine the impact of adjacent forms (metonymy and metaphorical metaphor with its various relationships in generating connotation and directing meaning. The research decided to be an applied study in examples of the Maqamat of Jalal al-Din al-Suyuti, as he is considered one of the creators who was unique in writing the art of Maqamat and excelled at it. The research aims to investigate Images based on juxtaposition in selected evidence from his maqamat in order to seek the secondary connotations of them in the context of their use. Its importance lies in shedding light on an important element of the literary language, and proving that Al-Suyuti in the art of maqamat has left a special literary imprint due to its various linguistic phenomena and connections. It is rich in cultural and heritage, and it should be noted that the research does not aim to theoretically establish the images of the juxtaposition and repeat the repeated ones, but rather it suffices with presenting a summary of them, then moving on to the analytical reading of the selected evidence from his maqamat, which show their main role in directing the meaning intended by the transmitter, and determining the connotations.To be delivered to the addressee.